2007
DOI: 10.1021/ja0748027
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Performance of Molecularly Imprinted Fluorescent Conjugated Polymer Materials

Abstract: Fluorescent conjugated polymers are an attractive basis for the design of low detection limit sensing devices owing to their intrinsic signal amplification capability. A simple and universal method to rationally control or fine-tune the chemodetection selectivity of conjugated polymer materials toward a desired analytical target would further benefit their applications. In a quest of such a method we investigated a general approach to cross-linked molecularly imprinted fluorescent conjugated polymer (MICP) mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(117 citation statements)
references
References 32 publications
3
114
0
Order By: Relevance
“…Furthermore, in contrast to the natural antibody, the substantial advantages of artificial counterparts are their mechanical and chemical robustness and their production by self-assembling processes without time-consuming and complex synthesis. Combining the high selectivity of molecular imprinting and the fluorescent properties of QDs could develop new method for target analyte recognition (Haupt et al, 1998;Carlson et al, 2006;Turkewitsch et al, 1998;Li et al, 2007Li et al, , 2010Tu et al, 2008). In such nanoparticles-based sensing systems, binding a target molecule is translated into a sensor signal and fluorescence intensity changes when a target 0956-5663/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in contrast to the natural antibody, the substantial advantages of artificial counterparts are their mechanical and chemical robustness and their production by self-assembling processes without time-consuming and complex synthesis. Combining the high selectivity of molecular imprinting and the fluorescent properties of QDs could develop new method for target analyte recognition (Haupt et al, 1998;Carlson et al, 2006;Turkewitsch et al, 1998;Li et al, 2007Li et al, , 2010Tu et al, 2008). In such nanoparticles-based sensing systems, binding a target molecule is translated into a sensor signal and fluorescence intensity changes when a target 0956-5663/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Li et al [18], for example, the use of molecularly imprinted polymer (MIP) improved the selectivity of the fluorescent determination of 2,4,6-trinitrotoluene. Due to the low levels of environmental pollutants in real samples, a sensitive method is necessary for routine analysis of these pollutants.…”
Section: Introductionmentioning
confidence: 88%
“…During the past ten years, the literatures on the development of MIP-based sensors, in particularly electrochemical (Riskin et al, 2008;) and optical (McDonagh et al, 2008;BasabeDesmonts et al, 2007;Li J. et al, 2007a;Feng et al, 2008) sensors, have been dramatically growing (Nilsson et al, 2007;Ramanavicius et al, 2006). It was found that the manufacture of composites consisting of molecularly imprinted conducting polymers results in obtaining materials that exhibit both predetermined selective molecular recognition and electrical conductivity (Deore et al, 2000).…”
Section: Mips In Chemical Sensingmentioning
confidence: 99%